Studies on adsorption of cr(vi) onto strychnos potatorum seed from aqueous solution. Issue 1 (18th August 2011) - Lakshmipathiraj, P.; Umamaheswari, S.; Raju, G. Bhaskar; Prabhakar, S.; Caroling, G.; Kato, S.; Kojima, T.
<x xml:space="preserve">Abstract</x> The removal of Cr(VI) from aqueous solution using the seeds of the plant species Strychnos potatorum was studied. The plant is popularly known as Nirmali tree, grown all over India. The dried Nirmali seeds were powdered and used as adsorbent. The SEM‐EDX and FT‐IR spectrum of the adsorbent revealed that the powder is fibrous in nature and contains functional groups such as —OH and —COOH. The zeta potential measurements indicated negative surface charge beyond the pH of 1.50. Batch type experiments were conducted to study the influence of pH and initial Cr(VI) concentration on the removal of Cr(VI) from aqueous solutions. Maximum removal of Cr(VI) was observed at pH 1.0. The adsorption equilibrium was attained within a sort contact time of 4 min and the maximum uptake of Cr(VI) was found to be 59 mg g−1. The influence of anions such as Cl−, NO3−, and SO42− on Cr(VI) removal was investigated and found that the removal was slightly affected in the presence of NO3− and SO42−. The rate of removal of Cr(VI) was found to obey pseudo second order rate equation. The high free energy value of adsorption (ΔG = −137 kJ mol−1) indicated that the adsorption of Cr(VI) on Nirmali seed powder was mainly attributed due to chemical and electrostatic interaction. © 2011 American Institute of Chemical Engineers Environ Prog, 32: 35–41, 2013.